PENGARUH PERSEPSI KONSUMEN DAN PROMOSI TERHADAP MINAT PEMBELIAN PRODUK PT. SUMBER LAUTAN REZEKI MEDAN - Jeffry Tanoto; Thomas Sumarsan Goh; Errie Margery (JURNAL BISNIS KOLEGA, 2021)
PT. Sumber Lautan Rezeki Medan is a company engaged in production and furniture sales. There are problems with the interest in purchasing furniture to customers which is indicated by furniture sales that are declining every month. Consumer perception in this company always has the view that the products marketed by this furniture company are more expensive compared to other furniture companies. The promotion problem at this company is less attractive to consumers because this company only applies promotions such as price discounts for some types of furniture when at the end and beginning of the year. This research uses descriptive quantitative research. The population in the study was 731 consumers with a sampling technique using the Slovin formula of 5% error tolerance in the sample of 259 respondent. Data analysis techniques using multiple linear regression analysis. Partially and simultaneously there is a positive and significant effect between the consumer perception and promotion variables on purchasing interest at PT. Sumber Lautan Rezeki Medan Product.Â Keywords: Consumer Perception, Promotion, Purchasing Interest